A case report: how to clarify fever with thrombocytopenia due to dengue or chronic liver disease? - Putra, Made Sukma; Ketut , Suryana (International Journal of Research in Medical Sciences, 2023)
Fever and thrombocytopenia mostly associated with dengue hemorrhagic fever. But on certain condition of fever with thrombocytopenia, we still seek another etiology such as chronic liver disease. How to clarify between thrombocytopenia in dengue and chronic liver disease.